2015
DOI: 10.1007/s00267-015-0638-2
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Long-Term Sustainability in Seminatural Forestry: A Broad Perspective Based on Woodpecker Populations

Abstract: We assessed ecological sustainability of seminatural forestry by analyzing 80-year dynamics and the current distribution of all woodpecker species in Estonia. We found that, despite the clear-cutting-based forestry system, woodpeckers inhabited commercial seminatural forests in substantial numbers, including the species generally considered vulnerable to timber harvesting. The only negative trend, a drastic decline in the Green Woodpecker, paralleled the loss of seminatural, wooded grasslands and is mostly an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…We use the term ''territory'', because middle spotted woodpeckers defend almost exclusive territories during March and April, with both sexes participating to similar degrees in territorial defense (Pasinelli et al 2001). On the basis of our long-term experience, we assumed that two registrations in the pre-breeding period was sufficient to accept a territory (Lõhmus et al 2016;Stachura-Skierczyńska and Kosiński 2016), and to exclude transient/floater birds (Pasinelli et al 2001;Robles and Ciudad 2012). Moreover, two visits allow an experienced observer to find almost 100% of territories in the pre-breeding period (Z. Kosiński unpubl.…”
Section: Woodpecker Occurrence Datamentioning
confidence: 99%
“…We use the term ''territory'', because middle spotted woodpeckers defend almost exclusive territories during March and April, with both sexes participating to similar degrees in territorial defense (Pasinelli et al 2001). On the basis of our long-term experience, we assumed that two registrations in the pre-breeding period was sufficient to accept a territory (Lõhmus et al 2016;Stachura-Skierczyńska and Kosiński 2016), and to exclude transient/floater birds (Pasinelli et al 2001;Robles and Ciudad 2012). Moreover, two visits allow an experienced observer to find almost 100% of territories in the pre-breeding period (Z. Kosiński unpubl.…”
Section: Woodpecker Occurrence Datamentioning
confidence: 99%
“…The woodpecker species in this study represent three different feeding strategies (Lõhmus et al 2016). First, there are two dead-wood dependent species, the White-backed Woodpecker and the Lesser Spotted Woodpecker.…”
Section: Discussionmentioning
confidence: 99%
“…These coastal areas are characterized by mild winters and few days with snow cover. Lõhmus et al (2016) found that the population density of the Grey-headed Woodpecker was vulnerable to prolonged periods of cold winters and deep snow. A period of low abundance was documented following three snowrich winters in 2009/2010, 2010(Lõhmus et al 2016.…”
Section: White-backed Woodpeckermentioning
confidence: 99%
“…We build on nearly 20 years of research on biodiversity in Estonian forests where we have used standard sampling designs to test the responses of species and assemblages to various influences of even-aged forestry (e.g., [15][16][17][18]). The Estonian context is suitable for general insight because it has, until recently, adopted a "semi-natural forestry" approach, which mitigates environmental impacts of even-aged forestry and forestry drainage by frequently using natural regeneration, tree retention, and low intensity of thinnings [19,20]. In addition to relatively intact species pools, a semi-natural context reveals species that depend on naturally developing forests (strict protection) from those, which are restricted to such forests only because of inadequate habitat provision in production stands [11,17,21].…”
mentioning
confidence: 99%